1994
DOI: 10.1111/j.1440-1746.1994.tb01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral zinc supplementation on metallothionein and superoxide dismutase concentrations in patients with inflammatory bowel disease

Abstract: Oxygen-derived free radicals may contribute to intestinal tissue damage in inflammatory bowel disease. The concentrations of metallothionein and superoxide dismutase, two copper and zinc containing proteins involved in the scavenging of free radicals; were previously found to be decreased in the intestinal mucosa of patients with this disorder. The plasma zinc concentration is often decreased also in these patients. Since zinc is reported to be an efficient inducer of metallothionein synthesis, and probably of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…30 -33 However, evidence that MT induction by Zn supplementation plays a major role in protection against nondiabetic injuries has been demonstrated. [17][18][19][20]28 We have also shown that Zn administration caused a marked MT synthesis in rabbit lymphocytes and in cultured human neuronal cells that provided a significant resistance to radiation-induced DNA damage and cell death. [37][38][39] In the present study, supplementation with Zn for 3 months provided a significant protective action on diabetic cardiomyopathy along with the significant induction of MT.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…30 -33 However, evidence that MT induction by Zn supplementation plays a major role in protection against nondiabetic injuries has been demonstrated. [17][18][19][20]28 We have also shown that Zn administration caused a marked MT synthesis in rabbit lymphocytes and in cultured human neuronal cells that provided a significant resistance to radiation-induced DNA damage and cell death. [37][38][39] In the present study, supplementation with Zn for 3 months provided a significant protective action on diabetic cardiomyopathy along with the significant induction of MT.…”
Section: Discussionmentioning
confidence: 86%
“…17,18 In addition, that MT upregulation in response to Zn supplementation prevents various pathogeneses has been documented in humans. 19,20 The present study therefore was undertaken to investigate the protective effects of Zn supplementation, with cardiac MT induction, on diabetic cardiomyopathy as a possible pharmaceutical approach to prevention of diabetic cardiovascular complications.…”
Section: Clinical Perspective P 554mentioning
confidence: 99%
“…Therefore it would be of interest whether local or systemic stimulation of MT-synthesis by zinc application would be clinical useful to decrease the damaging inflammatory process in CD and UC. Mulder et al [25] couldn´t find any effect on inflammation score and disease activity index of IBD-patients after 4 weeks therapy with oral zinc. However the study group was small and pre-treatment zinc concentrations were almost comparable to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…All these physiological functions occur through the action of proteins involved in the regulation of zinc homeostasis such as metallothioneins which bind zinc with high affinity but, at the same time, release free zinc ions in response to oxidative/nitrosative stress that modulates the expression of zinc-dependent genes, activates antioxidant enzymes and has impact on immune response [21]. Zinc may induce the synthesis of metallothionein that act as a scavengers of metals and free radicals [22,23]. The release of zinc from metallothioneins represents an intracellular response to stress.…”
Section: Evidence For the Role Of Oxidative Injury In Autism And The mentioning
confidence: 99%